Methodological Insights on Teachers’ Professional Agency in Narratives - Heikkilä Mirva (Oslo Metropolitan University, 2022)
This article presents post-structural narrative methodologies to examine teachers’ agency. According to previous research, agency is important for the learning and well-being of teachers. However, post-structuralism has questioned the assumption of agency as being located in the individual and has claimed a more entwined and relational perspective. The article disturbs clear-cut categorisations of teachers’ agency as strong or weak and argues for examining narrative practice because teachers use a variety of grammatical resources that are not inherently personal but are entwined with cultural narratives. This methodological approach reveals how teachers appear agentic and vulnerable at the same time. Thereby, it helps illustrate multifaceted views of the teaching profession.